Osteogenic differentiation of placenta-derived multipotent cells in vitro - Chih-Chien Cheng; Chih-Ang Chung; Li-Chiu Su; Chih-Cheng Chien; Yu-Che Cheng (Taiwanese Journal of Obstetrics & Gynecology, 2014)
Objective: Stem cells offer great potential for clinical therapeutic use because of their ability to rejuvenate and to differentiate into numerous types of cells. We isolated multipotent cells from the human term placenta that were capable of differentiation into cells of all three germ layers. Materials and methods: We examined the ability of these placenta-derived multipotent cells (PDMCs) to differentiate into osteoblasts (OBs) or OB-like cells. The PDMCs were treated with osteogenic medium (OM) consisting of dexamethasone, β-glycerol phosphate, and ascorbic acid. At sequential time intervals (0 day, 3 days, 6 days, 9 days, and 12 days) we measured several parameters. These included alkaline phosphatase (ALP) activity, alizarin red staining (ARS) to measure calcium deposition, messenger RNA (mRNA) expressions of osteogenesis-related transcription factor (Cbfa1), and calcium coordination protein (osteocalcin). These variables were used as indicators of PDMC osteodifferentiation. Results: We showed that ALP activity in the early stage of differentiation and calcium deposition were both significantly increased in PDMCs after OM induction. Moreover, the Cbfa1 and osteocalcin gene expressions were upregulated. The results suggested that OM induced an osteodifferentiation potential in PDMCs. Conclusion: PDMC-derived osteocytes provide a useful model to evaluate the mechanisms of key biomolecules and bioengineering processes.